The Cipete Vs Situbondo Feud (1983-1984): Study of Khittah NU Return and Its Impact on PBNU Political Policy - Harun, Hermanto; Nurjaman, Andri; Huda, Ali Anhar Syi'bul; Rasidin, Mhd.; Muna, Moh. Nailul (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This article aims to look at the history of the feud between the Cipete camp, namely the KH Idham Chalid camp and supported by NU politician cadres with the Situbondo camp supported by non-political scholars in the context of searching for NU identity (Khittah NU) and its implications for PBNU’s political policies during the leadership of Gus Yahya Cholil Staquf, both national politics and practical politics in the 2024 elections. This article is a library research study with historical methodology, namely heuristics, criticism, interpretation, and historiography. The research found that the conflict between the Situbondo camp and the Cipete camp was a tug-of-war over the search for NU’s identity, which was allegedly pushed very far into the realm of practical politics and neglected other fields. To settle the dispute, a reconciliation was made between the two camps in 1984, and both continued the NU congress in Situbondo, which gave birth to a new PBNU leadership, a return to the basic values of NU as a social organisation, withdrawing from various aspects of practical politics, and accepting the single principle of Pancasila. When viewed in the context of 2024, the PBNU led by Gus Yahya Cholil Staquf (period 2022 to 2027) is guided by the Khittah NU and stops all practical political activities, especially in the face of the 2024 elections. PBNU, under Gus Yahya’s leadership, asserted its neutrality and independence as a form of NU’s Khittah in all kinds of practical politics. The issue of PBNU’s alignment with one of the Presidential and Vice Presidential candidate pairs in the 2024 elections was dismissed and denied by PBNU. PBNU carries out national politics by ensuring the safety of Indonesia's religion, nation, and state, especially after the 2024 elections.